Evaluation of yield characters of marigold (Tagetes species) genotypes under summer condition in alluvial Gangetic plains of North India (Current Horticulture, 2024)
During the 2016 summer season, a study was conducted at the Department of Horticulture, Bihar Agricultural University,  Sabour, Bhagalpur, to evaluate 26 marigold (Tagetes species) genotypes, including 23 experimental lines and three controls. The  experiment followed a randomized complete block design with three replications. The results of the analysis of variance revealed  highly significant differences (p
Keywords: Morphological characters; High temperature; Summer season; Yield